Multi-wavelength deep-ultraviolet absorbance detector based upon program-controlled pulsing light-emitting diodes - Mikhail, Ibraam E; Hemida, Mohamed; Lebanov, Leo; Astrakhantseva, Snezhana; Gupta, Vipul; Hortin, Philip; Parry, John S; Macka, Mirek; Paull, Brett (Journal of chromatography. A, 2023)
A novel approach for multi-wavelength ultraviolet (UV) absorbance detection has been introduced employing a single board computer (SBC) with a field programmable gate array (FPGA), Red Pitaya SBC, to generate separated micro pulses for three deep-ultraviolet light-emitting diodes (DUV-LEDs), λmax = 235, 250, and 280 nm, along with data acquisition and processing via a custom-made program. The pulse set generation and data acquisition were synchronized using the SBC. The outputs of the three pulsing DUV-LEDs were combined and transmitted to the flow cell via a solarisation resistant trifurcated optical fiber (OF). An ultra-fast responding photodiode was connected to the optical-fiber-compatible flow cell to record the intensity of the DUV pulses. Upper limit of detector linearity (A95 %) was found to be 1917 mAU, 2189 mAU, and 1768 mAU at 235 nm, 250 nm, and 280 nm, respectively, with stray light ≤0.9 %. In addition, the effective path length (Leff) was estimated to be ≥98.0 % of the length of the used flow cell (50 mm). The new pulsed multi-LEDs absorbance detector (PMLAD) has been successfully coupled with a standard liquid chromatograph and utilized for the analysis of pharmaceuticals. Paracetamol, caffeine, and aspirin were simultaneously determined at 250, 280, and 235 nm, respectively, using the PMLAD. The absorbance ratios between the different wavelengths were applied to further confirm the identity of the studied compounds. Excellent linearity was achieved over a range of 0.1-3.2 µg/mL for paracetamol, 0.4-6.4 µg/mL for caffeine, and 0.8-12.8 µg/mL for aspirin with a regression correlation coefficient (r2) ≥ 0.99996. The quantitation limits (LOQs) were 0.10 µg/mL, 0.38 µg/mL, and 0.66 µg/mL for paracetamol, caffeine, and aspirin, respectively.
Keywords: Aspirin; Acetaminophen; Deep-ultraviolet absorption; kofein; Multi-wavelength detection; Chromatography, Liquid; Ultraviolet Rays; Caffeine; Red Pitaya; Pulsing light-emitting diodes; chromatografie kapalinová; High performance liquid chromatography; ultrafialové záření; paracetamol